SOCIALLY RESPONSIBLE MARKETING IN THE MARKET OF REHABILITATION AIDS - Kosar , N. S.; Melnyk, Kh. R. (The actual problems of regional economy development, 2025)
It has been established that socially responsible marketing is an integral part of the activities of modern enterprises, but its implementation depends on the characteristics of the goods offered. The purpose of the article is to study the key aspects of implementation of socially responsible marketing by sellers in the market of rehabilitation aids through the use of omnichannel marketing and reverse distribution channels in their activities. Considering the growing number of people with disabilities, these issues are of particular relevance today. To achieve the aim of the study, secondary marketing information on the rehabilitation equipment market was collected and analyzed, using the method of observing the activities of rehabilitation equipment sellers, benchmarking, systematization and comparison. The scientific novelty of the work lies in the development of the theoretical and methodological foundations of using the concept of socially responsible marketing by enterprises that are focused on people with disabilities. It has been found that in the process of purchasing goods under martial law, consumers prefer those brands that have implemented the principles of social responsibility in their activities. The article presents a study of sellers of rehabilitation aids in Lviv. It was found that all companies provide information to consumers about their products on their websites, but not all of them provide the opportunity to purchase goods online. Among the services provided by such sellers, one can highlight expert consultations. At the same time, some sellers, such as Medical Shop LLC, use reverse distribution channels, buying back used wheelchairs, and also offer rehabilitation equipment rental services, which increases its availability to those in need. In this area, a recommended initiative for resellers of rehabilitation equipment would be to develop a platform for people with disabilities where they can obtain used rehabilitation equipment, subject to proper quality control by sellers of similar goods, or buy new goods from resellers and domestic manufacturers. This demonstrates the practical value of this study.